“Navigating through the digital swamp”: Assessing SME propensity for online marketplaces - Gonçalves, M.; Ferreira, F.; Dabić, M.; Ferreira, J. (Review of Managerial Science, 2024)
Digital technology has produced deep changes in the business world. However, companies have a hard time understanding consumers’ changing needs and new consumption patterns, especially small and medium-sized enterprises that currently face growing challenges in an era characterized by a lack of time and information overload. New mechanisms must be found that not only can keep businesses competitive in digital environments but can do so in innovative and sustainable ways. This study sought to address this issue by adopting a process-oriented approach and developing a decision-support tool for SMEs that are considering joining online marketplaces. The proposed analysis model helps these companies decide whether they are ready to take advantage of these digital platforms or whether they have to take action to improve in specific areas of their business operations. The model-building process relied on a combination of cognitive mapping and the best–worst method. An expert panel was recruited to identify the most relevant factors determining SME readiness to join online marketplaces. The model was applied to a set of real companies to assess their propensity for online marketplaces. The practical applicability of this decision-support system was then discussed in a consolidation session with a member of Portugal’s Agência Nacional de Inovação (National Innovation Agency), who acknowledged the strong potential of the proposed model.